A survey on the educational qualifications of AM radio broadcasters in Iloilo Cty. - Armada, Cornelio Jude Catahay
This study A survey on the Educational Qualifications of AM Radio Broadcaster in Iloilo aims to (1) identify the educational qualifications of AM Radio Broadcasters in Iloilo City; (2) determine the number of AM Radio Broadcasters in Iloilo City earned a degree in Mass Communication/Broadcasting and other communication-relatedcourses; (3) and identify the qualifications considered by AM Radio Stations in hiring broadcast practitioners., According to the data gathered by the researchers, almost all of the respondents have a high educational attainment. It showed that out of 42 respondents, 39 are graduates of a 4-year course. Only one practitioner is Underraduate while the other two are graduates of a 2-year course. Five graduates of communication-related courses were also able to have a post-graduate study. The results of the study show that there are only 24 graduates of Mass Communication, Broadcast communication and other communication-related courses working int he industry. Meanwhile, almost all of the AM radio station managers ranked a graduate of 1 4-year course as the most considered qualification in hiring broadcast practitioners. Other qualifications considered are communication and writing skills, mental/intellectual capacity/ analytical, work ethics/attitude/character, talent and abilities, voice quality/diction, civil service eligibility, and experience.